Novel nicotinamide analog as inhibitor of nicotinamide N-methyltransferase. Issue 5 (1st March 2018) - Ruf, Sven; Hallur, Mahanandeesha Siddappa; Anchan, Nisha K.; Swamy, Indu N.; Murugesan, Karthikai Raj; Sarkar, Sayantani; Narasimhulu, Lokesh Kananti; Putta, V.P. Rama Kishore; Shaik, Shama; Chandrasekar, Devaraj Venkatapura; Mane, Vishal Subhash; Kadnur, Sanjay Venkatachalapathi; et al.
Graphical abstract: Compound12 Human/mouse NNMT enzymatic inhibition (IC50 ): 0.58/4.5 µM. Inhibition of MNA in U2OS/3T3L1 cell based assay: 0.3/2.1 µM. Human/mouse metabolic stability (% remaining after 30 m): 85/69. In vivo target engagement (MNA reduction, 2 h): ∼80%. Abstract: Nicotinamide N-methyltransferase (NNMT) has been linked to obesity and diabetes. We have identified a novel nicotinamide (NA) analog, compound 12 that inhibited NNMT enzymatic activity and reduced the formation of 1-methyl-nicotinamide (MNA), the primary metabolite of NA by ∼80% at 2 h when dosed in mice orally at 50 mg/kg.